Optimization of Patient Management During the COVID-19 Pandemic: Chest CT Scan and PCR as Gatekeepers of the Radiation Therapy Workflow - Sun, Roger; Ammari, Samy; Bockel, Sophie; Achkar, Samir; Merad, Mansouria; Dercle, Laurent; Rivera, Sofia; Chargari, Cyrus; Deutsch, Eric (Frontiers in Oncology, 2020)
The coronavirus disease 2019 (COVID-19) has been spreading rapidly and is likely to last over time. Since numbers of patients are asymptomatic and cancer patients may be more vulnerable to the COVID-19 disease, screening strategies may be helpful in order to ensure care continuity as well as patients and healthcare providers safety. We discuss here the potential interest of systematic chest-CT and rt-PCR screening for patients undergoing radiotherapy.